Ofício de professor/a: artesania da relação pedagógica escolar - Oliari, Gilberto (2021)
This thesis was developed in the Graduate Program in Education at the Federal University of Santa Maria, in Research Line 2: Educational public policies, educational practices and their interfaces, and is part of an investigative and reflective movement that seeks to defend the school and its characteristic elements, in times of transformation from the act of teaching to the facilitation of learning. In this sense, the central theme of the research is the pedagogical relationship established between teacher and student. It seeks to defend an artisanal perspective in the establishment of this relationship, focusing on the argument about the power of the word. Three characteristics of artisanal production are systematically addressed (at different times): material awareness (SENNETT, 2013), the ritual of artisanal making (SENNETT, 2012) and the artisanal workshop (SENNETT, 2013). These arguments are presented in an approximation of ideas and concepts about the pedagogical relationship to affirm the thesis that the artisanal production mode can enable the teacher to establish the pedagogical relationship in which his responsibility for the common world can be inferred (ARENDT, 2007), committing to the recognition of the Other’s discourse (LÉVINAS, 2011). This was produced from a methodology called bibliographical walker artisan of hermeneutic inspiration. It is concluded that the teacher can be a craftsman in the pedagogical relationship as long as he/she recognizes himself as such and produces this relationship based on the principles of craftsmanship.